2012
DOI: 10.1021/jp2104819
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Molecular Dynamics Simulation Approach for Lipophilic Drug Incorporation into Polymer Micelles

Abstract: Polymer micelles can be used to facilitate the aqueous solubilization of lipophilic, poorly water-soluble compounds and drugs. Even if the evaluation of the efficiency of drug incorporation into such micelles can be tested experimentally, a theoretical approach based on molecular simulation can constitute a useful tool that reduces time and cost. Here we present a promising method, based on molecular dynamics simulation, for the calculation of the Flory-Huggins interaction parameters as a measure of the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 56 publications
1
75
0
Order By: Relevance
“…Recent years have witnessed a growing interest in the field of biodegradable polymers and, consequently, in computational activities to explore various molecular properties of biodegradable polymers . Poly(lactide) (PLA) and its copolymers are among the most widely used synthetic biodegradable polymers for drug encapsulation and delivery with several products for controlled release of proteins or peptides on the market .…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have witnessed a growing interest in the field of biodegradable polymers and, consequently, in computational activities to explore various molecular properties of biodegradable polymers . Poly(lactide) (PLA) and its copolymers are among the most widely used synthetic biodegradable polymers for drug encapsulation and delivery with several products for controlled release of proteins or peptides on the market .…”
Section: Introductionmentioning
confidence: 99%
“…However, vitamin D3 exhibited the highest loading even with less strong H-bonding and π-π interactions. Thus, the study revealed the significant role of subtle structural characteristics (e.g., size, flexibility, and rigidity) in drug loading and suggested the computations of drug-polymer pairs would be a powerful prescreening tool in the development and optimization FiGURe 3 | Snapshot of cyclosporin A (in van der waals surface) and PeG-hexPLA (PeG in blue and hexPLA in red) mixture (Kasimova et al, 2012). Reproduced with permission from American Chemical Society.…”
Section: Amphiphilic Copolymersmentioning
confidence: 99%
“…A linear relationship was observed between the solubility and mass fraction for the four drugs. This method could be further utilized to estimate drug incorporation efficiency upon structural modification of polymer chains (Kasimova et al, 2012). The above computational studies reported drug solubility, miscibility, and compatibility in different copolymers.…”
Section: Amphiphilic Copolymersmentioning
confidence: 99%
“…1 molecule) there is no significant change in micellar size. Consequently, we will just investigate the size and shape of micelle for systems [6][7][8][9].…”
Section: The Size Of Micellesmentioning
confidence: 99%
“…There are many theoretical and experimental studies on the solubilization and solubilization location of hydrophobic materials such as drugs [7,8], dyes [9,10], oils [11] and other organic compounds [12][13][14][15][16] within the micelles. Recognizing of these solubilization sites is very essential and helps us to have a better understanding of solubilizate characteristics in micelle, to investigate reaction mechanism in micellar systems and to design the micellar systems to reach the favorite properties.…”
Section: Introductionmentioning
confidence: 99%